Synthesis, Characterization, and In Vitro and In Vivo Evaluations of cellulose hydrogels enriched with larrea tridentata for regenerative applications - Tovar Carrillo, Karla Lizette (2020)
Introduction. Tissue engineering is an elementary necessity for several applications in the biomedical field through the use of several biopolymers derived from plants. Larrea tridentata (LT) is a very used plant for various medicinal applications with interesting properties; however, its use into cellulose hydrogels for possible regenerative therapeutics is still limited. Cellulose films could be applied in medical field as wound healing, scaffold for connective tissue for periodontal applications, and so on. The aim of this study was to evaluate the mechanical properties and in vivo and in vitro biocompatibility of cellulose hydrogels that have been enriched with LT in a rat model. Methods. By in vivo and in vitro assays, the concentration of LT was varied from 1 to 5 wt%, respectively. Hydrogel films were implanted intramuscularly into female Wistar rats, 250 g in weight and aged 2 months, to analyze their cytocompatibility and biocompatibility. Results. No case showed any evidence of inflammation or toxicity. Regarding cell morphology and adhesion, the prepared LT cellulose films had better cytocompatibility values than when polystyrene (PS) dishes were used as the control. In all cases, the results suggest that the addition of LT to the hydrogel films did not affect their cytocompatibility or biocompatibility properties and increases their clinical application due to the reported uses of LT. Conclusions. Cellulose hydrogel films enriched with LT have the potential to be used in the biomedical field acting as regenerative scaffolds